Blood pressure and kidney size in term newborns with intrauterine growth restriction - Matsuoka, Oscar Tadashi [UNESP]; Shibao, Simone [UNESP]; Leone, Cléa Rodrigues [UNESP] (Associação Paulista de Medicina - APM, 2007)
CONTEXT AND OBJECTIVE: Low birth weight is associated with higher blood pressure in childhood and adulthood. The aim of this study was to investigate the influence of intrauterine growth restriction (IUGR) on newborn systolic blood pressure (SBP). DESIGN AND SETTING: Prospective comparative study at Neonatal and Intensive in Clinical Pediatrics Division, Maternity Hospital in Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo. METHODS: 35 newborns with IUGR and 35 without IUGR were compared. Healthy term newborns without malformations, with Apgar score at fifth minute > 6 were included. Birth weight, kidney weight/birth weight ratio, kidney weight (ultrasound scan), plasma renin activity (PRA) and SBP evolution were analyzed during the first month of life (on 1st, 3rd, 7th and 30th days). RESULTS: SBP evolution, kidney weight/birth weight ratio and PRA did not differ between the two groups. In newborns with IUGR, SBP presented positive correlations with birth weight (r = 0.387 p = 0.026) and BMI (r = 0.412 p = 0.017) on the 7th day of life. Positive correlations with birth weight (r = 0.440 p = 0.01) and birth length (r = 0.386 p = 0.026) were also seen on the 30th day. There was an inverse correlation on the 7th day between SBP and kidney weight/birth weight ratio (r = -0.420 p = 0.014), but this did not persist to the end of the month. CONCLUSIONS: IUGR seems not to have any influence on SBP, PRA or kidney weight among term newborns during their first month of life.

CONTEXTO E OBJETIVO: O baixo peso ao nascimento está associado à pressão arterial mais elevada na criança e no adulto. O objetivo foi avaliar a influência do retardo do crescimento intra-uterino (RCIU) na pressão arterial sistólica de recém-nascidos (PAS). TIPO DE ESTUDO E LOCAL: Estudo prospectivo, realizado no berçário anexo à maternidade, Instituto da Criança, Hospital das Clínicas da Universidade de São Paulo. MÉTODOS: 35 recém-nascidos (RN) com RCIU e 35 RN sem RCIU foram avaliados em um estudo prospectivo. Os critérios de inclusão foram: recém-nascidos no termo, saudáveis, sem malformações e índice de Apgar de quinto minuto > 6. Parâmetros antropométricos (peso ao nascimento, relação comprimento renal/peso ao nascimento), dimensões renais (pela ultra-sonografia), dosagem da atividade da renina plasmática (ARP) e a evolução da PAS foram analisadas durante o primeiro mês de vida (no 1º, 3º, 7º e 30º dias de vida). RESULTADOS: A evolução da PAS, relação peso renal/peso ao nascimento e ARP não apresentaram diferença entre os dois grupos. Em recém-nascidos com CIUR, a correlação entre PAS e PN (r = 0,387 p = 0,026) e IMC (r = 0,412 p = 0,017) foi positiva no 7º dia de vida. No 30º dia de vida, a correlação com PN (r = 0,440 p = 0,01) e comprimento ao nascimento (r = 0,386 p = 0,026) também foi positiva. Houve correlação negativa entre a PAS do 7º dia e a relação peso do rim/peso ao nascimento (r = - 0,420 p = 0,014), porém, esta correlação não persistiu ao longo do primeiro mês de vida. CONCLUSÕES: RCIU parece não influenciar a PAS, a atividade de renina plasmática ou o peso renal em recém-nascidos no termo durante o primeiro mês de vida.
Pressão arterial e tamanho renal em recém-nascidos no termo com restrição de crescimento intra-uterino
Keywords: Blood pressure; Fetal growth retardation; Newborn infant; Kidney; Renin; Pressão arterial; Retardo do crescimento fetal; Recém-nascido; Rim; Renina